Implementation of Home Learning Strategies in Private Primary Schools During Pandemic Covid-19 - Ekowati, Dyah Worwirastri; Suwandayani, Beti Istanti (Universitas Pendidikan Ganesha, 2021)
The Indonesian government established a Learning From Home (BDR) policy related to learning during the Covid-19 pandemic. This article aims to analys learning strategies from home during the Covid-19 pandemic in Indonesian private elementary schools. The research method was carried out in a descriptive qualitative manner. Collecting data through interviews, observation, and documentation. Data analysis in this qualitative research was started when the data collection took place, and after the data collection was completed within a certain period. The data analysis implemented content analysis techniques. Activities in data analysis included data reduction which summarised, chose the main points, focused on the important things, as well as looking for themes and patterns. Moreover, data display organised the data, arranged in a relationship pattern, so that it would be more easily understood. . The research subjects were the principal (key informant), teacher, students, 2 guardians. The results of the analysis show that BDR is carried out using blended learning (synchronous and asynchronous). Synchronous implementation using social media (WA, IG, Zoom, Gmeet) and school learning applications with a duration of 1-3 hours. Meanwhile, asynchronous is done by sending assignments/projects/questions via social media or the PANDHAWA application every day or once a week. Different strategies are following the readiness of schools, infrastructure, human resources, teachers, students, and parents. With various BDR strategies implemented, schools can overcome deficiencies and improve and develop the quality of learning.